The transformation of commons in the Afar region in Ethiopia - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Traditional communal landholding has long been prevalent in the Afar region of Ethiopia, accommodating the interests of different user groups for many generations. This form of land ownership, which entails use of pastoral resources scattered over a wide area to produce livestock, is attributable to ecological conditions characterized by frequent drought. The harsh environment in which herders raise their livestock requires constant mobility to regulate resource use via a common property regime. In contrast to the mobile way of life characterizing pastoralism, agriculture as a sedentary activity is only marginally present in the lowlands of the Afar region. However, the traditional land use system is changing because of pressures from both governmental policy and natural events such as drought. Communal land ownership in Afar is under pressure as a result of state intervention (political risks) and natural challenges (natural risks).